The Level of Beef Cattle Farmers' Readiness for Livestock Intensification Program Surrounding Baluran National Park Area - Zazin Fahresi Alamanda; Siti Azizah; Hary Nugroho (Department of Forestry, Faculty of Agriculture, University of Lampung, 2022)
Wild grazing is the main problem faced by Baluran National Park (BNP) management. Sidomulyo Hamlet contributed to wild grazing by the cattle number of 2,220 heads. The research aims to assess the community readiness for the intensification program to reduce wild grazing in BNP and formulate alternative strategies to program successfully. The study was conducted in Sidomulyo Hamlet, Sumberwaru Village, Situbondo Regency, from June to October 2021. The location was chosen purposively, considering that it is one of the hamlets directly adjacent to the BNP. The method used a qualitative approach using Community Readiness Model by interviewing 12 key informants, consisting of the representative of BNP management, local government, and local farmers. Data were collected through interviews using a semi-structured questionnaire under Community Readiness Model Handbook. Data were analyzed using Community Readiness Assessment. The results showed that the community readiness score related to the livestock intensification program was 4.43. The level of beef cattle community readiness at the preplanning stage, the program is still in the initial planning stage, aiming to increase awareness of the farmer community with ideas that can reduce the problem. Alternative strategies that should be carried out are: introducing information about the problem, communicating with community leaders, reviewing the efforts made to determine targets and success rates, conducting focus group discussions to discuss the problem and develop strategies, and increasing media exposure. Keywords: Baluran National Park, Community Readiness Model, conservation, wild grazing